Three-dimensional core-shell alginate microsphere for cancer hypoxia simulation in vitro - Ruan, Yejiao; He, Lingyun; Chen, Jiamin; Wang, Jinfeng; Zhao, Shujing; Guo, Xiaoling; Xie, Yao; Cai, Zhenzhai; Shen, Xian; Li, Chao (Frontiers in Bioengineering and Biotechnology, 2023)
Hypoxia is one of the major causes for cancer resistance and metastasis. Currently, it is still lack of convenient ways to simulate the in vivo hypoxic tumor microenvironment (TME) under normoxia in vitro. In this study, based on multi-polymerized alginate, we established a three-dimensional culture system with core-shell structure (3d-ACS), which prevents the oxygen diffusion to a certain extent, thereby simulating the hypoxic TME in vivo. The cell activity, hypoxia inducible factor (HIF) expression, drug resistance, as well as the related gene and protein changes of the gastric cancer (GC) cells were investigated in vitro and in vivo. The results demonstrated that the GC cells formed organoid-like structures in the 3d-ACS and manifested more aggressive growth and less drug responses. Our study provides an accessible hypoxia platform in laboratory with moderate configuration and it may be applied in studies of the hypoxia induced drug resistances and other preclinical fields.